A Music Room of One's Own: Discursive Constructions of Girls-only Spaces for Learning Popular Music - Björck, Cecilia (Girlhood Studies, 2013)
This article elaborates on discursive constructions of girls-only settings through the spatial metaphor of a room of one's own, as articulated in round-table discussions among staff and participants from girl-centered music programs in Sweden. The idea of a separate room refers to spaces for collective female empowerment as well as for individual knowledge acquisition and creativity. These spaces are constructed so as to provide the possibility for exploration, subjectivity, and focus, by offering (partial and temporary) escape from competition and control, from a gendered and gendering gaze, and from distraction. Girl-centered programs are also discussed as paradoxical because they function as gender-neutral when seen from the inside, but gender-specific when seen from the outside.
Publisher: Berghahn Journals Section: Girlhood Studies

Safe Space: The Riot Grrrl Collection - Keenan, Elizabeth K.; Darms, Lisa (Archivaria, 2013)
Riot Grrrl, an early-1990s teen feminist movement, adopted punk’s DIY modes of expression to encourage girls to address their shared oppression. The Riot Grrrl Collection, held at New York University’s Fales Library & Special Collections, documents the movement through the personal papers of those who were active in its formative years. This article uses the lens of feminist “safe space” to look at the collection from two perspectives: that of its founder, Lisa Darms, who is senior archivist at Fales, and that of ethnomusicologist Elizabeth Keenan, a scholar who has worked extensively with the collection. The concept of safe space was crucial to the all-girl meetings, dance parties, and bands that formed the foundation of Riot Grrrl. The authors argue that the safe space of Riot Grrrl created an intimate counter-public – that is, a space where girls established a feminist community through shared texts – but one that sometimes worked against its own intentions: boundaries erected for safety sometimes led to exclusion along lines of race, class, or gender identity. The authors extend the idea of safe space to issues of collection building from and within activist communities; to ideas of intimacy and privacy as they play out for donors, for researchers, and in the special collections reading room; and to the tension between the desire for access to activist history versus the requirements of archival preservation. The article examines how iterations of safe space are enacted across the personal papers in the Riot Grrrl archive, through both the materials themselves and their place in the archive. RÉSUMÉ Riot Grrrl, un mouvement du début des années 1990 pour adolescentes féministes, s’est inspiré du mouvement punk pour adopter les modes d’expression du « Do it yourself (DIY) », dans le but d’encourager les adolescentes à aborder leur oppression commune. La collection Riot Grrrl, détenue par la Fales Library & Special Collections de l’University New York, documente le mouvement grâce aux documents personnels de celles qui en étaient actives durant ses premières années. Cet article se sert du concept féministe du « lieu sûr » (« safe space ») afin d’examiner la collection à partir de deux perspectives : celle de sa fondatrice, Lisa Darms, qui est archiviste supérieure à Fales, et celle de l’ethnomusicologue Elizabeth Keenan, une spécialiste qui a travaillé en profondeur avec cette collection. Le concept du lieu sûr était crucial pour les adolescentes lors de leurs réunions et soirées dansantes et pour leurs groupes musicaux qui ensemble ont contribué à la fondation de Riot Grrrl. Les auteurs soutiennent que le lieu sûr de Riot Grrrl a créé un « contre-public intime » – c’est-à-dire un espace dans lequel les adolescentes ont pu établir une communauté féministe par l’entremise de textes partagés – mais un contre-public qui opérait parfois contre ses propres intentions : les limites imposées pour délimiter le lieu sûr ont parfois mené vers des exclusions basées sur la race, les classes sociales ou l’identité de genre. Les auteures élargissent le concept du lieu sûr aux questions liées à la création de collections par des communautés militantes et dans ces milieux; aux idées de l’intimité et de la vie privée auxquelles sont confrontés les donateurs et les chercheurs dans la salle de lecture des collections spéciales; et à la tension entre le désir d’avoir accès à l’histoire militante et les besoins liés à la conservation archivistique. Cet article examine comment l’itération du lieu sûr se fait par rapport aux documents personnels des archives Riot Grrrl, tant du côté des documents eux-mêmes que de leur place dans les archives.

Female, Mosher, Transgressor: A 'Moshography' of Transgressive Practices within the Leeds Extreme Metal Scene - Riches, Gabrielle; Lashua, Brett; Spracklen, Karl (IASPM Journal, 2013)
This paper examines and reconceptualises transgression in the Leeds extreme metal music subculture through theories of performance, embodiment and spectacle. The spectacle, for Debord (1967), is a social relation that is alienating and mediated by images, visuals, and technology. At a live extreme metal concert fans subvert social norms, challenge gendered expectations, and disregard norms of etiquette and decency. Moshing is the most visible and sensuous example of transgression within the extreme metal scene. It is an aggressive, physically demanding performance which embodies resistance to the impersonal and disillusioning world of the spectacle (Halnon, 2004). The pit is a transgressive space that is itself transgressed by women who participate in this masculine, chaotic space, disrupting the homosocial bonds of male solidarity (Gruzelier, 2007). This paper offers an ethnographic account of a female metal fan participating in the transgressive practice of moshing within the Leeds metal music scene – a moshography.
Number: 1
Keywords: Moshpits; embodiment; extreme metal music; performance ethnography; spectacle; transgression

Why producers of music use discourses of consumption (and why we shouldn't think that makes them prosumers) - Cluley, Robert (Arts Marketing: An International Journal, 2013)
Purpose ‐ The purpose of this paper is to demonstrate how people making music represent their production activities using images of consumption. Design/methodology/approach ‐ Supporting evidence is based on in-depth interviews with musicians and support personnel. The data are structured through a thematic analysis. Findings ‐ The paper argues that consumption serves as a discursive resource that allows cultural producers to make sense of production activities which do not conform to an image of production as an alienated form of labour. Originality/value ‐ Relating the analysis to the ongoing attempts to conceptualise cultural producers through the concept of prosumption, the paper concludes that there are limits to cultural producers' abilities to represent their production activities as production rather than a structural change in social or economic organisation, as suggested by some consumer researchers.

Why unpaid interns are bad for the music industry (the Guardian, 2013)
Helienne Lindvall: Big US record labels are being sued by former interns who worked for free – how do their UK counterparts measure up?
Section: Media

Q&A: Veteran Music Video Director Diane Martel on Her Controversial Videos for Robin Thicke and Miley Cyrus - Ducker, Eric (Grantland, 2013)
Heads up: NSFW videos and websites are occasionally linked to throughout this post, so watch who’s watching your monitor. Robin Thicke’s “Blurred Lines” and Miley Cyrus’s “We Can’t Stop…

Why Music Matters - Hesmondhalgh, David (John Wiley & Sons, 2013)
Listen to David Hesmondhalgh discuss the arguments at the core of 'Why Music Matters' with Laurie Taylor on BBC Radio 4's Thinking Allowed here. In what ways might music enrich the lives of people and of societies? What prevents it from doing so? Why Music Matters explores the role of music in our lives, and investigates the social and political significance of music in modern societies. First book of its kind to explore music through a variety of theories and approaches and unite these theories using one authoritative voice Combines a broad yet theoretically sophisticated approach to music and society with real clarity and accessibility A historically and sociologically informed understanding of music in relation to questions of social power and inequality By drawing on both popular and academic talk about a range of musical forms and practices, readers will engage with a wide musical terrain and a wealth of case studies
Google-Books-ID: lDL4rKLCHmgC
Keywords: Music / General; Music / History & Criticism

Looking for Something New: The Provision of Popular Music Studies Degrees in the UK - Cloonan, Martin; Hulstedt, Lauren (IASPM Journal, 2013)
This article reports the findings of some commissioned research, which was conducted by the authors in 2012. The research sought to examine the extent of Popular Music Studies (PMS) undergraduate programmes in the United Kingdom, determine their key differences, report the findings and make recommendations to the funders about its future policies for PMS practitioners. We report our findings and the implications for PMS practitioners.
Number: 2
Keywords: Popular Music; Teaching; UK; Undergradute

Dark Side of the Tune: Popular Music and Violence - Johnson, Professor Bruce; Cloonan, Professor Martin (Ashgate Publishing, Ltd., 2013)
Written against the academically dominant but simplistic romanticization of popular music as a positive force, this book focuses on the 'dark side' of the subject. It is a pioneering examination of the ways in which popular music has been deployed in association with violence, ranging from what appears to be an incidental relationship, to one in which music is explicitly applied as an instrument of violence. A preliminary overview of the physiological and cognitive foundations of sounding/hearing which are distinctive within the sensorium, discloses in particular their potential for organic and psychic violence. The study then elaborates working definitions of key terms (including the vexed idea of the 'popular') for the purposes of this investigation, and provides a historical survey of examples of the nexus between music and violence, from (pre)Biblical times to the late nineteenth century.The second half of the book concentrates on the modern era, marked in this case by the emergence of technologies by which music can be electronically augmented, generated, and disseminated, beginning with the advent of sound recording from the 1870s, and proceeding to audio-internet and other contemporary audio-technologies. Johnson and Cloonan argue that these technologies have transformed the potential of music to mediate cultural confrontations from the local to the global, particularly through violence. The authors present a taxonomy of case histories in the connection between popular music and violence, through increasingly intense forms of that relationship, culminating in the topical examples of music and torture, including those in Bosnia, Darfur, and by US forces in Iraq and Guantánamo Bay. This, however, is not simply a succession of data, but an argumentative synthesis. Thus, the final section debates the implications of this nexus both for popular music studies itself, and also in cultural policy and regulation, the ethics of citizenship, and arguments about human rights.
Keywords: Music / Ethnomusicology; Music / Instruction & Study / Theory

The Continuum of Sexual Violence: Women’s Accounts of Victimization in Urban Nightlife - Kavanaugh, Philip R. (Feminist Criminology, 2013)
Despite the fact that a substantial amount of research has been conducted on sexual victimization among youth and young adults with active night lives, few of these studies have provided an analysis of the varied types of victimization that have occurred. I attempt to fill this gap with a qualitative analysis of women’s accounts of sexual victimization. Based on the substantive content of these women’s accounts, a three-part typology was generated, comprised of: (a) competing definitions of the situation, (b) opportunistic predation, and (c) involuntary incapacitation. Implications of the findings are discussed.
Publisher: SAGE Publications
Keywords: accounts; sexual assault; sexual victimization; unwanted sexual contact

Music, Style, and Aging: Growing Old Disgracefully? - Bennett, Andy (Temple University Press, 2013)
The image of the aging rock-and-roller is not just Paul McCartney and Mick Jagger on stage in their sixties. In his timely book Music, Style, and Aging , cultural sociologist Andy Bennett explains how people move on from youth and effectively grow older with popular music.For many aging followers of rock, punk, and other contemporary popular genres, music is ingrained in their identities. Its meaning is highly personal and intertwined with the individual's biographical development. Bennett studies these fans and how they have changed over time–through fashions, hairstyles, body modification, career paths, political orientations, and perceptions of and by the next generation.The significance of popular music for these fans is no longer tied exclusively to their youth. Bennett illustrates how the music? that "mattered" to most people in their youth continues to play an important role in their adult lives–a role that goes well beyond nostalgia.

A woman's worth: Analyzing the sexual objectification of Black women in music videos - Ward, L. Monique; Rivadeneyra, Rocio; Thomas, Khia; Day, Kyla; Epstein, Marina (The sexualization of girls and girlhood: Causes, consequences, and resistance, 2013)
One arena where images of sexually objectified women are especially prevalent is the world of music videos. Music videos represent an important area of study, both because of their popularity with younger viewers (Ashby & Rich, 2005) and because love and sex predominate as themes (Andsager & Roe, 1999; Arnett, 2002). What we seek to do here is to take a closer look at the nature and impact of the portrayal of women in music videos, focusing, in particular, on sexually objectifying images. How frequently do objectifying images occur? What messages about femininity do these images convey to girls? What is their demonstrated impact on girls and young women? Given the current popularity of rap and hip-hop music, we focus our attention on their portrayals of African American women. We address these issues via four pathways. First, we summarize findings from existing research concerning the nature of gender portrayals in music videos. Second, we turn our attention to African American artists and summarize findings about the images of black women in music videos. Third, we present new data from an analysis we conducted of the sexual content in black music videos, providing both quantitative and thematic analyses. Finally, we summarize findings about the demonstrated impact of music video exposure on young viewers' gender beliefs and body image concerns. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: Blacks; Human Females; Music; Myriam; Objectification; Sex Roles